The role of asymmetrical prominent veins sign in early neurological deterioration of acute ischemic stroke patients - Kuankuan Huang; Jianfang Liu; Wenwei Yun; Yin Cao; Min Zhang (Frontiers in Neurology, 2022)
Background and purposeAsymmetrical prominent veins sign (APVS) often appears on susceptibility-weighted angiography (SWAN) images in patients with acute stroke. Early neurological deterioration (END) is highly correlated with survival prognosis in patients with ischemic stroke. This study sought to explore the relationship between APVS and END in patients with acute stroke.MethodsThe subjects retrospectively enrolled in this study were patients with acute ischemic stroke in the middle cerebral artery supply area. All patients underwent head MRI, including the SWAN sequence, within 7 days of stroke symptom onset. END was defined as clinical deterioration or recurrence within 72 h after ischemic stroke. The volume of infarction on diffusion-weighted imaging was measured. Univariate and multivariate analyses were used to analyze the relationship between APVS and END. Spearman correlation between APVS grades and infarct volume, white matter hyperintensity (WMH) volume, and offending vessel were also analyzed.ResultsA total of 157 patients with middle cerebral artery infarct between September 2018 and April 2020 were included in the study. APVS appeared on MRI in 84 of 157 patients, and 34 of 157 patients were diagnosed with END. In patients with END, the proportion of severe APVS was higher than in patients without END (P = 0.001, x2 = 14.659). Patients with END were older and had a larger volume of infarct and WMH than patients without END (all P < 0.05). After adjustments were made for related risk factors of END, the severity of APVS was still related to END (OR = 2.56, 95% CI, 1.38–4.75; P for trend = 0.003). Spearman correlation showed that APVS grades were positively related to infarct volume (r = 0.289, P < 0.001) and 3-month modified Rankin Scale score (r = 0.203, P = 0.011) and negatively related to offending vessels (r = −0.170, P = 0.034).ConclusionAPVS may be an important predictor of END in patients with acute ischemic stroke.